Percutaneous microwave ablation of uterine fibroids: correlation between shrinkage and trend symptoms. Issue 1 (1st February 2021) - Ierardi, Anna Maria; Petrillo, Mario; Fumarola, Enrico Maria; Coppola, Andrea; Angileri, Salvatore Alessio; Garanzini, Enrico; Silipigni, Salvatore; Pesapane, Filippo; Marconi, Anna Maria; Carrafiello, Gianpaolo
Abstract: Purpose: To assess a correlation between the shrinkage of the fibroid and the course of the symptoms. Material and methods: Fourteen patients with symptomatic uterine leiomyomas (mean fibroid volume: 111.45 cm 3 ) underwent percutaneous microwave ablation. Contrast-enhanced MRI follow-up was performed before and after treatment to evaluate the volume shrinkage. Two scores obtained from the Uterine Fibroids Symptom and Quality of Life questionnaire were used to perform a clinical follow-up to evaluate the symptoms and the quality of life at baseline, and at 3, 6 and 12 months after treatment. Results: All patients were treated, no complications occurred. During a mean MR follow-up of 8.1 months we observed shrinkage of the fibroids in all patients (mean 70.3 cm 3 ). During 12 months clinical follow-up, we observed a significant improvement of symptoms and an excellent improvement of quality of life ( p  < .001). Conclusion: Uterine fibroids percutaneous microwave ablation is a safe tool to obtain a significant improvement in quality of life for all the patients of our cohort.